Peran Kepuasan Sebagai Variabel Intervening pada Kualitas Produk terhadap Minat Beli Ulang Konsumen Kedai Jukung Bali - Maya Nur Akmalia; Kartika Anggraeni Sudiono Putri (IPM2KPE, 2024)
The aim of the research is to investigate and analyze the role of satisfaction as an intervening variable in the relationship between product quality and consumer repurchase interest at Kedai Jukung Bali. This research aims to understand the extent to which consumer satisfaction mediates the influence of product quality on repurchase intention, with the hope of providing valuable insight for management and contributing to the understanding of consumer behavior in the industry. This research is a type of quantitative research with a descriptive approach and the sample used was 200 respondents with the criteria of having visited and made purchases in the last year. The method for calculating the sample size uses the Malhotra (2009) formula with purposive sampling technique. The results of this research prove that: 1) Product quality has a positive and significant effect on repurchase interest, 2) Product quality has a positive and significant effect on consumer satisfaction, 3) Consumer satisfaction has a positive and significant effect on repurchase interest, 4) Product quality has a positive effect and significant on repurchase intention with consumer satisfaction as an intervening variable mediated by consumer satisfaction at Kedai Jukung, Jembrana Regency, Bali. In conclusion, Kedai Jukung is expected to maintain the appearance of the product, menu variants and improve the taste of each menu in order to encourage consumers to come and recommend Kedai Jukung to others. Keywords: Product Quality, Consumer Satisfaction, Repurchase Intention